Hukum Mendirikan Partai Politik Perspektif Islam: Refleksi Islam Politik Klasik dan Modern - Amin Heri Susanto (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2020)
When the law establishment of political parties is controversial, this article tries to analyze based in the early history of Islam by identifying groups (hizb) who demand the leadership for the their articulation rights are encompassed, including the Khawarij, Mu'tazilah and Shi'ite groups are identified as a reflection of classical political Islam. The reflection of modern political Islam is marked by an aggregation of contemporary needs that cannot be denied the necessity for the establishment of political parties by looking issues in Egypt and Indonesia in the early era of independence. The difference of views among scholars and ijma 'ulama is an interesting discussion in determining istimbath about the law of establishing an Islamic perspective party. AbstrakKetika hukum pendirian partai politik menjadi kontroversi, artikel ini mencoba menganalisis berdasarkan peristiwa sejarah diawal Islam dengan mengidentifikasi kelompok (hizb) yang menuntut estafet kepemimpinan sebagai bentuk artikulasi agar hak-hak mereka terwadahi, termasuk munculnya golongan Khawarij, Mu'tazilah dan Syi'ah yang diidentifikasi sebagai refleksi Islam politik klasik. Adapun refleksi Islam politik modern ditandai dengan agregasi kebutuhan kontemporer yang tidak bisa dipungkuri terhadap keharusan pendirian partai politik dengan melihat isu-isu di Mesir dan Indonesia di era awal kemerdekaan. Perbedaan pandangan dikalangan cendekiawan serta ijma' ulama menjadi diskusi menarik dalam menentukan istimbath tentang hukum mendirikan partai perspektif Islam.